The Monk Parakeet in the Western Palearctic: Distribution, Feeding Ecology, Public Perception and Management Implications. - Postigo-Sánchez, José Luis (UMA Editorial, 2024)
This thesis investigates the changes in ecological, behavioral, and societal aspects of the monk parakeet (Myiopsitta monachus), focusing on its invasion patterns. Chapter one compares the population dynamics of monk parakeets in the Mediterranean and Atlantic regions. The research reveals that Mediterranean populations grow and spread at a faster rate than their Atlantic counterparts. This rapid growth in the Mediterranean presents a significant threat to local agriculture and biodiversity. The thesis recommends that immediate management actions be taken, especially in regions with smaller populations where eradication is still feasible. Chapter two examines the dietary habits of monk parakeets in Mediterranean urban environments, highlighting their seasonal adaptability. Their reliance on anthropogenic food sources and grass year-round demonstrates dietary flexibility that aids survival. The study suggests reducing food availability, particularly human-provided sources, to control their population. Chapter three focuses on Israel, where monk parakeets are expanding into rural areas, particularly near agricultural lands, leading to crop damage. The population in Israel is growing exponentially, and the thesis emphasizes the need for urgent management efforts to prevent further agricultural damage, recommending rapid eradication before the situation escalates. Chapter four analyzes changes in public opinion, using surveys from Barcelona over 15 years. As awareness of the species' negative impacts grows, support for control measures increases. The research advocates public education campaigns to promote acceptance of management strategies.
Keywords: Especies exóticas invasoras - Control - Tesis doctorales; Cotorras argentinas - Distribución geográfica - Tesis doctorales; Cotorras argentinas - Hábitos y conducta - Tesis doctorales; Invasive species; Ecological change; Dispersion; Public opinion; Crop damage